2017
DOI: 10.1016/j.stem.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Activation during Repeated Regeneration Impairs Somatic Stem Cell Maintenance

Abstract: Summary The balance between self-renewal and differentiation ensures long-term maintenance of stem cell (SC) pools in regenerating epithelial tissues. This balance is challenged during periods of high regenerative pressure and is often compromised in aged animals. Here we show that TOR signaling is a key regulator of SC loss during repeated regenerative episodes. In response to regenerative stimuli, SCs in the intestinal epithelium of the fly and in the tracheal epithelium of mice exhibit transient activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 61 publications
9
86
0
Order By: Relevance
“…This response is observed upon infection with enteropathogens, as well as in response to DNA damage, oxidative stress, or surfactant challenge (4,11,12). In cases in which the challenge is temporary, such as during infection with the mild enteropathogen Erwinia carotovora carotovora 15 (Ecc15), ISCs return to quiescence upon reestablishment of a functional epithelium, and the animal can thus survive multiple challenges [albeit, with a progressive loss of stem cells (42)]. The activation of ISCs results in an asymmetric division, which allows self-renewal of ISCs, as well as the generation of either EE-or enterocyte-committed postmitotic progenitor cells called enteroblasts (4,12).…”
Section: Regulation Of Intestinal Stem Cell Proliferationmentioning
confidence: 99%
“…This response is observed upon infection with enteropathogens, as well as in response to DNA damage, oxidative stress, or surfactant challenge (4,11,12). In cases in which the challenge is temporary, such as during infection with the mild enteropathogen Erwinia carotovora carotovora 15 (Ecc15), ISCs return to quiescence upon reestablishment of a functional epithelium, and the animal can thus survive multiple challenges [albeit, with a progressive loss of stem cells (42)]. The activation of ISCs results in an asymmetric division, which allows self-renewal of ISCs, as well as the generation of either EE-or enterocyte-committed postmitotic progenitor cells called enteroblasts (4,12).…”
Section: Regulation Of Intestinal Stem Cell Proliferationmentioning
confidence: 99%
“…28,29,31,50,51 Indeed, we found that induction of cell senescence is required for trans-differentiation. Rapamycin, which is a well-established inhibitor for cell senescence, 32,33,52 antagonized the induction of senescence in fibroblasts by IGFBP7 and abolished reprogramming into osteoblasts. It is possible that activation of other signaling pathways by IGFBP7 also contributes to osteogenic phenotype in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin also inhibited agerelated basal cell decline in the mouse trachea and restored basal cell numbers when given to older mice. 49 While more research is required to extend these results to humans, these results suggest that it is possible to restore stem cell activity and rejuvenate cells in aged animals.…”
Section: Addressing Age-related Stem Cell Dysfunctionmentioning
confidence: 99%